A FAITH IN ACTION: ISLAMIC ETHICAL PERSPECTIVE ON THE GLOBAL HUMANITARIAN CRISIS - nurhasanah, muwahidah; Idharudin, Abdul Jabar (LPPM STAI Muhammadiyah Probolinggo, 2026)
Today’s global humanitarian crises—ranging from armed conflicts, refugee displacement, extreme famine, to ecological disasters—require an ethical framework capable of balancing universal human values with religious moral principles. Islamic ethics, grounded in the concept of maqāṣid al-sharī‘ah, which emphasizes the protection of life (ḥifẓ al-nafs), intellect (ḥifẓ al-‘aql), and human dignity (ḥifẓ al-‘ird), offers an important perspective in responding to contemporary humanitarian challenges. However, studies examining the direct application of Islamic ethics in modern humanitarian practices, particularly within digital spaces and online communities, remain limited. This research employs a netnography approach to explore digital interactions, narratives, and discourses related to humanitarian actions inspired by Islamic ethical values across social media platforms, community forums, and websites of Islamic philanthropic organizations. Data were collected through online participatory observation, analysis of digital conversations, and virtual in-depth interviews with humanitarian activists. The findings reveal that the values of rahmah (compassion), ‘adl (justice), and ukhuwwah insāniyyah (human solidarity) serve as key moral foundations, while social media functions not only as a fundraising tool but also as a space where Islamic ethics are interpreted and mobilized to address global issues such as climate crises, forced migration, and inequality.